Moteriškojo linksniavimo daiktavardžių kamienų mišimas uteniškių tarmėje - Rinkauskienė, Regina (Baltistica, 2004)
THE MERGER OF THE FEMININE DECLENSION IN THE EASTERN LITHUANIAN (UTENA) DIALECTThe article deals with morphological features of the Eastern Lithuanian (Utena) dialect of the Lithuanian language. There is a tendency for the merger of the feminine stems: ēand i̯ā, ē and ā, ā and a, ē and (i̯)a. The analysis shows that the merger of stems is influenced by the phonetic development of the dialect, semantic fields and the neutralization of the collective plural.
Keywords: dialektologija; uteniškiai; daiktavardis